Modern surgical treatment of azoospermia. Issue 1 (27th January 2023) - Brant, Aaron; Schlegel, Peter N.
Abstract : Purpose of review: To review noteworthy research from the last 2 years on surgical management of azoospermia. Recent findings: The recommended treatments for nonobstructive and obstructive azoospermia have not appreciably changed. However, recent level-1 evidence has reinforced superiority of micro-dissection testicular sperm extraction over sperm aspiration in men with nonobstructive azoospermia, and several studies have identified genetic and other clinical factors that may aid in selecting candidates for testicular sperm extraction. Machine learning technology has shown promise as a decision support system for patient selection prior to sperm retrieval as well a tool to aid in sperm identification from testis tissue. Summary: Most men with obstructive azoospermia who desire fertility can be offered either surgical reconstruction or sperm retrieval. For men with nonobstructive azoospermia, sperm retrieval with microdissection testicular sperm extraction remains the gold standard treatment. Uncovering more genetic causes of nonobstructive azoospermia may aid in properly counseling and selecting patients for microdissection testicular sperm extraction. Neural networks and deep learning may have a future role in patient selection for surgical sperm retrieval and postprocedural sperm identification.